Online Learning For Primary Level / Madrasah With Online Applications In Min 2 Serdang Bedagai - Suyanto; Surbakti, Nurul Maulida; Sitorus, Syahriol; Siregar, Rosman; Zahedi (Talenta Publisher, 2021)
The online learning system is still having problems. As a result of the observations of the USU team, several obstacles were felt not only by the teachers at MIN 2 Serdang Bedagai but also by students and parents. The problems that occur are quite diverse. Starting from limited signal, limited devices suitable for online learning, to the lack of technological knowledge of teachers and students on online applications that support the teaching and learning process. There are various online applications available today, such as Google Classroom, Zoom, Google Meet, Youtube, and others. These various online applications play an important role in helping students and teachers in the distance learning process. The USU team conducted training using the online application Google Classroom and Zoom. Google Classroom and Zoom were chosen because they are easier for the teacher to implement, besides that the two online applications facilitate coordination and communication between teachers and students, so that the material being taught can be discussed more easily, more freely and can be updated more quickly. In this community service, Online Learning training was conducted for the Elementary School / Madrasah Ibtidaiyah Level with Various Online Applications at MIN 2 Serdang Bedagai. This community service has reached the implementation stage of training which begins with the initial survey stage, provision of training modules and also training. The next stage is monitoring and evaluation and feedback.Â